Impacts of the World Heritage List inscription: a case study of Kaiping Diaolou and Villages in China - Han, Wei; Cai, Jianming; Wei, Yigang; Zhang, Ying; Han, Yan (International Journal of Strategic Property Management, 2020)
This study aims to investigate the overall impacts of the World Heritage List (WHL) inscription in China from different socioeconomic aspects. Kaiping Diaolou and Villages was chosen as the case study because the long period of preparation for WHL inscription led to residents’ deep understanding of its heritage values. Results are as follows. (1) Cultural cognition, sense of belonging, community cohesion and infrastructure were positively improved by the WHL inscription, whereas damage to the community cultural environment slightly increased. (2) In the economic domain, the WHL inscription had generated positive (increase in tourism development and villagers’ income and employment and solution to the Diaolou property rights problem) and negative impacts (worse tourism development, unequal income and unsolved property rights problems). (3) The WHL inscription improved the ecological environment and people’s attention to environmental protection. Although it also caused environmental damage due to an increase in tourists. (4) The positive impacts on the political domain were reflected by government leadership, community participation and plan and legislation, whereas the negative impacts included limited community participation and insufficient planning. Innovations of this study include constructing a theoretical framework to evaluate the impacts of WHL inscription, analysing the present factors of WHL inscription’s impacts and providing development suggestions.First published online 22 October 2019